Juvenile delinquency: a sociological perspective - Thompson, William E. (Rowman & Littlefield, 2021)
"This books takes a sociological approach to discussing delinquency as it relates to and emerges from the youth's family, neighborhood, school, peer group, social class, and overall cultural and social environment. The authors incorporate contributions from sociologists, psychologists, social workers, criminologists, and other specialists who have sought to understand, explain, control, and prevent juvenile delinquency"--